Brain metastasis of choriocarcinoma presenting as multiple intracranial hematomas: A case report. Issue 37 (September 2018) - Wang, Dawei; Shu, Hansheng; Zhang, Qiujian; Zhang, Hui; Qing, Chao; Wang, Hao
Abstract: Rationale: Choriocarcinoma is the most malignant type of gestational trophoblastic neoplasia. Brain metastasis is the main cause of death and disability in choriocarc- inoma patients. Brain metastasis of choriocarcinoma easily invades the vessel wall to form microaneurysms, so we have reason to believe that multiple intracerebral hemorrhage is related to neoplastic intracranial microaneurysms. Patient concerns: We report a rare case of brain metastasis of choriocarcinoma that caused six hemorrhages in four lesions within 50 days and anterior cerebral artery aneurysm. Diagnoses: We diagnosed multiple intracerebral hematoma, choriocarcinoma and intracranial aneurysms. Interventions: Evacuation of hematoma by craniotomy. Outcomes: The patient finally asked to terminate the treatment and was discharged. One month later, the patient died of upper gastrointestinal bleeding. Lessons: more than 20 cases of oncotic aneurysm from choriocarcinoma have been reported in the English literature, but few had multiple hematomas. Therefore, this case is unique. Brain metastasis of choriocarcinoma should be considered when patients experience unexplained cerebral hemorrhage, especially repeated intracranial hemorrhage in women of childbearing age. Early and intensive treatment can help achieve a better prognosis and avoid a fatal outcome. Multiple intracranial hematomas are related to neoplastic intracranial microaneurysms.